The Concept of Happiness in Djarum 76 “Yang Penting Hepii..” - Fredy Dwi Saputra (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This thesis mainly deals with the process of signification and metaphor in order to reveal the concept of happiness in Djarum 76 video commercial with its tagline “Yang Penting Hepii..”. The focus of the writer’s analysis is the verbal and visual expression in the video commercial as the writer uses Barthes’s process of signification and Lakoff’s and Johnson’s theory of metaphor in analysing the data. Those Barthes’s, Lakoff’s and Johnson’s theories helped the writer analyse the use of verbal and visual expression in the advertisement, then, figured out the concept of happiness in Djarum 76 video commercial. The writer analyses a video commercial  of  Djarum  76  entitled  “Jangkrik”. This  research  used  descriptive qualitative approach to describe the concept of happiness in the video commercial of Djarum 76. From the analysis, the writer found out that the video commercial of Djarum 76 uses process of signification to associate happiness with laughter. In doing so, Djarum 76 used verbal expression to build the patterned plot while the visual expression pictures elements of happiness within each videos to evoke laughter. In conclusion, the use of verbal and visual expression is aimed to make the audiences laugh which then associated with happiness.